Multivariable calculus - Larson, Roland E.; Hostetler, Robert P.; Edwards, Bruce H. (Brooks/Cole, Cencage Learning, 2012)
A comprehensive calculus course program that integrates and coordinates print, media, and technology products for successful teaching and learning